Association between triglyceride-glucose index and cardiovascular disease in US adults with chronic kidney disease: a population-based study - Lijia Liu; Hui Sun; Lan Yi; Gang Wang; Yanqin Zou (BMC Cardiovascular Disorders)
Abstract Objectives Triglyceride-glucose (TyG) index, which is a valuable measure of insulin resistance, has been found to have predictive value for cardiovascular disease (CVD). However, its relationship with CVD among individuals with chronic kidney disease (CKD) has not been thoroughly investigated. This study focused on examining the relationship of the TyG index and CVD among CKD patients in United States. Methods 3507 eligible participants from the National Health and Nutrition Examination Survey (2003–2018) were surveyed in this study. Methods such as multivariable logistic regression analysis and smooth curve fitting were employed to estimate how the TyG index is linked to CVD in CKD populations. Subgroup and interaction analyses were conducted in order to figure out potential moderating effects of various factors. Results In this cross-sectional study which based on a population with CKD, 29.5% of patients also had CVD. An independent and positive link of TyG and CVD was revealed (OR 1.213, 95% CI 1.059, 1.389). This association was nonlinear, with a threshold effect observed at a TyG index of 8.98. The results of subgroup analysis suggested that the relationships of TyG and CVD differed according to CKD stage: (OR 1.048, 95% CI 0.857, 1.282) in CKD stages 1–2; (OR 1.267, 95% CI 1.030–1.560) in stage 3; and (OR 2.131, 95% CI 1.224–3.709) in stages 4–5. Interaction analyses further suggested the potential moderating effects of CKD stage. Additionally, among specific CVD types, only coronary heart disease (CHD) had a significant and positive relationship with TyG (OR 1.617, 95% CI 1.123, 2.327). Conclusions TyG index was identified to be independently and positively related to the likelihood of CVD, specifically in populations with an eGFR < 60 mL/min/1.73 m². The association had a threshold effect. The results highlight the potential of the TyG index as a tool for screening and risk assessment of CVD in populations suffering from CKD, warranting further investigation.